Finite Element Analysis of Spinal Cord Stress in a Single Segment Cervical Spondylotic Myelopathy - Yang, Shaofeng; Qu, Luqiang; Yuan, Lijie; Niu, Junjie; Song, Dawei; Yang, Huilin; Zou, Jun (Frontiers in Surgery, 2022)
Background: Spinal cord ischemia is largely caused by cervical spondylotic myelopathy (CSM), which has a corresponding biomechanical basis. Finite element analysis of spinal cord stress in diseased segments of CSM was performed to provide a biomechanical basis for the pathogenesis of CSM. Methods: A single segment (C4-5) in a patient with CSM was selected for mechanical simulation of three-dimensional (3D) computed tomography scanning, and a 3D finite element model of the cervical vertebra was constructed. Based on the patient’s age, sex, height, weight, and other parameters, a finite element analysis model of an individual with healthy cervical vertebrae in our hospital was selected as the control to compare the stress changes between the patient and control groups in the analysis of the cervical vertebrae under anterior flexion, posterior extension, lateral flexion, and rotating load in the diseased spinal cord segment. Results: In the CSM patient, the diseased segment was C4-5. Under loading conditions of forward flexion, posterior extension, left flexion, right flexion, left rotation, and right rotation, the maximum stress on the spinal cord in the control group was 0.0044, 0.0031, 0.00017, 0.00014, 0.0011, and 0.001 MPa, respectively, whereas those in the spinal cord in the CSM group were 0.039, 0.024, 0.02, 0.02, 0.0194, and 0.0196 MPa, respectively. Conclusion: The maximum stress on the diseased segments of the spinal cord in the CSM group was higher than that in the control group, which contributed to verifying the imaging parameters associated with spinal cord compression stress.